Performance test of a parabolic reflector solar cooker in the Lhokseumawe Region - Faisal, Faisal; Setiawan, Adi; Sayuthi, Muhammad; Suryadi, Suryadi; Syukri, Syukri (Journal of Mechanical Engineering and Fabrication, 2025)
The utilization of solar energy as a renewable energy source is becoming increasingly important to reduce dependence on fossil fuels. One of its applications is the parabolic reflector solar cooker, which harnesses solar radiation for cooking purposes. This study aims to evaluate the performance of a solar cooker equipped with a parabolic reflector through a water heating test. The study presents an analysis of the performance of a solar cooker using a parabolic reflector collector. The solar reflector was constructed from mirror fragments arranged to form a parabolic shape with a surface area of 1.05 m². The experiment was conducted in the Lhokseumawe region, Aceh Province, Indonesia, located at coordinates 5°12’11.01’’ N and 97° E, with an altitude of 18.3 m above sea level. Performance measurements were carried out using a water heating method with a vessel containing 3.2 kg of water placed at the focal point of the reflector. The solar radiation received by the collector was reflected toward the focal point, heating the water directly. The results showed that the water temperature increased to 82.4 °C within 60 minutes, from 12:00 to 13:00 local time (WIB). The overall efficiency of the solar cooker was found to be 33.9%. These findings indicate that the parabolic reflector solar cooker has strong potential as an environmentally friendly alternative energy source suitable for application in tropical regions